A novel electro-chemotactic approach to impact the directional migration of transplantable retinal progenitor cells. (August 2019) - Mishra, Shawn; Peña, Juan S.; Redenti, Stephen; Vazquez, Maribel
Abstract: Photoreceptor degeneration is a significant cause of visual impairment in the United States and globally. Cell replacement therapy shows great promise in restoring vision by transplanting stem-like cells into the sub-retinal space as substitutes for damaged photoreceptors. However, vision repair via transplantation has been limited, in large part, by low numbers of replacement cells able to migrate into damaged retinal tissue and integrate with native photoreceptors. Projects have used external chemical fields and applied electric fields to induce the chemotaxis and electrotaxis of replacement cells, respectively, with limited success. However, the application of combined electro-chemotactic fields in directing cells within biomaterials and host tissue has been surprisingly understudied. The current work examined the ability of combined electro-chemotactic fields to direct the migration of transplantable retinal progenitor cells (RPCs) in controlled microenvironments. Experiments used our established galvano-microfluidic system (Gal-MμS) to generate tunable chemotactic concentration fields with and without superimposed electric fields. Result illustrate that combination fields increased the distance migrated by RPCs by over three times that seen in either field, individually, and with greater directionality towards increasing gradients. Interestingly, immunofluorescence assays showed no significant differences in the distribution of the total and/or activated cognate receptor of interest, indicating that changes in ligand binding alone were not responsible for the measured increases in migration. Bioinformatics analysis was then performed to identity potential, synergistic mechanistic pathways involved in the electro-chemotaxis measured. Results indicate that increased RPC migration in electro-chemotactic fields may arise from down-regulation of cell adhesion proteins in tandem with up-regulation of cytoskeletal regulation proteins. These comprehensive results point towards a novel migration-targeted treatment that may dramatically improve transplantation outcomes as well as elucidate unreported synergy across biological mechanisms in response to electro-chemotactic fields. Highlights: Combinatory fields of chemotactic and elecric fields increased RPC migration by more than three times of either field alone. No changes in the polarization or up-regulation of the cognate receptor were measured during tests of RPC migration. Bioinformatics analysis implicates Rap1 and Adherins pathways as possible control mechanisms for the enhanced RPC migration. Pathway predictions were validated via loss-of-function assay inhibiting Top2B.